A pilot study into the effects of music therapy on different areas of the brain of individuals with unresponsive wakefulness syndrome - Steinhoff, Nikolaus; Heine, Astrid Maria; Vogl, Julia; Weiss, Konrad; Aschraf, Asita; Hajek, Paul; Schnider, Peter; Tucek, Gerhard (Frontiers in Neuroscience, 2015)
The global cerebral network allows music “to do to us what it does”. While the same music can cause different emotions, the basic emotion of happy and sad songs can, nevertheless, be understood by most people. Therefore, the individual experience of music and its common effect on the human brain is a challenging subject for research. Various activities such as hearing, processing and performing music provide us with different pictures of cerebral centers in PET. In comparison to these simple acts of experiencing music, the interaction and the therapeutic relationship between the patient and the therapist in Music Therapy (MT) provide us with an additional element in need of investigation. In the course of a pilot study, these problems were approached and reduced to the simple observation of pattern alteration in the brains of four individuals with Unresponsive Wakefulness Syndrome (UWS) during MT. Each patient had three PET investigations: (i) during a resting state, (ii) during the first exposure to MT, and (iii) during the last exposure to MT. Two patients in the MT group received MT for 5 weeks between the 2nd and the 3rd PET (three times a week), while two other patients in the control group had no MT in between. Tracer uptake was measured in the frontal, hippocampal, and cerebellar region of the brain. With certain differences in these three observed brain areas, the tracer uptake in the MT group was higher (34%) than in the control group after five weeks. The preliminary results suggest that MT activates the three brain regions described above. In this article, we present our approach to the neuroscience of music therapy and discuss the impact of our hypothesis on music therapy practice, neurological rehabilitation of individuals in UWS and additional neuroscientific research.